IN LOVING MEMORY OF TAN SRI DATO’ DR. M. THAMBIRAJAH, THE ACADEMIC, INSPIRER AND REFORMER, 1942 -2025 - Sivachandralingam Sundara Raja (SEJARAH: Journal of the Department of History, 2025)
IN LOVING MEMORY OF TAN SRI DATO’ DR. M. THAMBIRAJAH, THE ACADEMIC, INSPIRER AND REFORMER, 1942 -2025